Assessment of the Performance of Regency and City Governments in Central Java Through Characteristics and Level of Financial Health - Aini, Nanda Hanizah Nur; Zulfikar (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine the effect of Local Own Source Revenue , Capital Expenditure , Dependency Level, and Fiscal Balance Funds on Local Government Financial Performance, with Financial Health as a moderator variable . The research was conducted on regency and municipal governments in Central Java Province using Local Government Financial Statements for the 2022–2024 period . A quantitative approach with a causal research design was employed . The sampling technique used was saturated sampling, in which all regency and municipal governments in Central Java Province were included as research Samples . Data were analyzed using multiple linear regression and moderated regression analysis , preceded by classical assumption tests to ensure the validity of the regression model. The results indicate that Local Own Source Revenue has a positive and significant effect on Local Government Financial Performance, while Capital Expenditure does not have a significant effect . The Dependency Level has a negative effect on Local Government Financial Performance, indicating that higher dependence on central government transfers tends to reduce financial Fiscal performance​ Balance Funds are found to have a significant effect on Local Government Financial Performance, reflecting their important role in supporting regional fiscal capacity . Furthermore , the moderated regression analysis shows that Financial Health does not moderate the relationship between Local Own Source Revenue , Capital Expenditure , Dependency Level, and Fiscal Balance Funds on Local Government Financial Performance. These findings suggest that improvements in local government financial performance is not solely determined by financial health conditions , but are also influenced by the effectiveness of revenue management and fiscal policy implementation at the regional level. This study is expected to contribute to the empirical literature on public sector accounting and provide insights for local governments in formulating more effective and sustainable financial management policies .